Оrgan-preserving surgery for breast cancer - D. D. Pak; E. A. Rasskazova (Опухоли женской репродуктивной системы, 2014)
The paper describes the experience in treating 435 breast cancer patients undergoing organ-preserving operations with and without plastic repair. Both the patients’ tissues and thir combination with a silicone endoprosthesis were used for repair. The specific features of a recurrence were analyzed after organ-preserving surgery depending on the stage, treatment method (surgical or combination) and histogenesis of a tumor.